Financial Literacy, Risk Tolerance, and Risk Perception as Determinants of Investment Decisions: A Study of Mutual Fund Investors in Indonesia - Sabina Adilia (CV. Era Digital Nusantara, 2025)
This study examines the influence of financial literacy, risk tolerance, and risk perception on investment decisions among mutual fund investors in Palembang, Indonesia. Primary data were collected from 98 respondents using purposive sampling and analyzed through Structural Equation Modelling (SEM) with SmartPLS 4. The results indicate that financial literacy does not significantly affect investment decisions, while risk tolerance and risk perception have positive and significant effects. The novelty of this research lies in simultaneously testing cognitive and psychological factors in the context of mutual fund investors in Indonesia. Theoretical contributions reinforce the role of risk tolerance and perception in investment decision-making, while practical implications provide insights for fund managers and regulators to improve investor education and risk management strategies.